The first SSR-based assessment of genetic variation and structure among Pinus laricio Poiret populations within their native area. (1st November 2016) - Bonavita, S.; Vendramin, G. G.; Bernardini, V.; Avolio, S.; Regina, T. M. R.
Abstract : Pinus laricio Poiret is the most widespread conifer occurring in Calabria (Sila and Aspromonte Massifs), Sicily (Mount Etna) and Corsica. Particularly, Calabrian laricio pine forests are strongly related to complex geological history, lithological and climatic characteristics and long human exploitation of the Sila territory, of which they are the most emblematic element. As far as we know, the P. laricio populations from their main range areas have never been thoroughly studied at the molecular level. This article reports on the first deep analysis of the genetic variability and structure of individuals from populations located in Calabria, Sicily and Corsica using both chloroplast and nuclear microsatellite markers. Significant variation within populations and low differentiation among populations were found by means of molecular variance estimates for the both types of markers. Bayesian clustering analyses revealed an unexpected grouping of P. laricio populations with individuals from Sila and, particularly, those from the Natural Reserve of Fallistro, have been identified as genetically distinct. Temporal genetic analysis in three large P. laricio populations also showed that there were no differences in genetic diversity levels over time; however, it allowed to recognize populations that deserve to be considered as a high priority for suitable preservation and management.